Traditional lore on the healing effects of therapeutic plants used by the local communities around Simien Mountains National Park, northwestern Ethiopia - Endalkachew Seraw; Yirgalem Melkamu; Getinet Masresha (BMC, 2024)
Abstract Background Simien Mountain National Park is a world heritage site with spectacular landscapes and rich in floral diversity. Exploring the plethora of conventional wisdom regarding therapeutic flora for sustainable use and drug development is a timely endeavor. Thus, the present study was aimed at investigating therapeutic plant uses and conservation practices by the local communities dwelling in the vicinity of the Park. Methods Eighty randomly selected general informants and 20 purposefully selected key informants were used to collect the traditional lore from 10 purposefully selected kebeles that border the Park. Data were collected using face-to-face interviews, guided field walks, group discussions and market surveys. Descriptive statistics were used to analyze the basic information collected from the informants. An independent sample t test was computed to compare the knowledge variations among different informant groups. Clustering and ranking techniques were employed to validate traditional wisdom of informants. Results Significant differences in traditional wisdom (P < 0.05) were observed only between general and key informants. Hundred thirteen therapeutic plant species belonging to 56 families were recorded. Asteraceae was the most species-rich family (10%). The majority of therapeutic species were collected from the wild (77%). Herbs and roots were the most preferred habit (47%) and plant parts (37%) for remedy preparation, respectively. Pounding was the most common preparation method (50.1%). The most frequently practiced route of administration was the oral route (48.1%). The highest Informant Consensus Factor (ICF) value (84%) was recorded for respiratory and febrile illnesses. Rumex nepalensis was the most preferred for the treatment of wounds, and Olea europaea subsp cuspidata was the first-ranked multipurpose plant. Conclusion The Park is rich in therapeutic species serving as a refuge for many endemic and endangered species associated with the local community rich medicinal traditional lore. Erosion of therapeutic plants, verbal transfer of the traditional wisdom and young generation negligence in acquiring traditional lore led to the deterioration of the long tradition of using therapeutic plants for health care. Endangered multipurpose therapeutic plants like Echinops kebericho should get conservation priority. Therapeutic plants with the highest ICF and fidelity level could be candidates for drug development.